Measurement of active drag forces during swimming - Hollander, A. P.; Groot, G. de; van Ingen Schenau, G. J.; Toussaint, H. M.; Best, H. de; Peeters, W.; Meulemans, A.; Schreurs, A. W. (Journal of Sports Sciences, 1986)
In order to measure active drag during front crawl swimming a system - M.A.D. - has been designed, built and tested. The system provides a good method of studying active drag and its relation to anthropometric variables and swimming technique.